The effect of mitochondrial ATP-sensitive potassium channels on apoptosis of chick embryo cecal cells by Eimeria tenella. (April 2015) - Yang, Sha-sha; Zheng, Ming-xue; Xu, Huan-cheng; Cui, Xiao-zhen; Zhang, Yan; Zhao, Wen-long; Bai, Rui
Highlights: We applied primary chick embryo cecal cells as host cells in vitro experiments. E. tenella- infected cells after diazoxide treatment underwent less apoptosis. Activities of caspases 9 and 3 were less activated in diazoxide-treated cells. MitoKATP channels play a key role in protecting cells from apoptosis by E. tenella. Abstract: The objective of this study was to investigate the effect of mitochondrial ATP-sensitive potassium (mitoKATP ) channels on apoptosis induced by Eimeria tenella . At 24, 48, 72, 96 and 120 h after Eimeria tenella infection, TUNEL assays and translation of phosphatidyl serines to the host cell plasma membrane surface showed that diazoxide-treated chick embryo cecal cells underwent less apoptosis ( P < 0.05), while light microscopy showed that infection rates of treated cells were higher ( P < 0.01) than untreated cells. Caspase 9 and caspase 3 of infected cells were activated less ( P < 0.01) in diazoxide-treated cells than untreated cells. These results indicate that opening mitoKATP channels can protect chick embryo cecal cells from mitochondria-dependent apoptosis induced by Eimeria tenella by inhibiting activations of caspase 9 and caspase 3.